Complications of Endoscopic Retrograde Cholangiopancreatography: How to Avoid and Manage Them - Szary, Nicholas M. (Millennium Medical Publishing, 2013)
Endoscopic retrograde cholangiopancreatography (ERCP) is a therapeutic procedure used to treat problems associated with biliary and pancreatic diseases. The benefits of ERCP over surgical treatment are well documented; however, complications including infection, pancreatitis, hemorrhage, and perforation can occur even in expert hands. Several factors, such as patient selection, skill of the operator, and the complexity of the procedure, can add to the intrinsic risks of ERCP This review outlines the current knowledge regarding ERCP complications and solutions for improved outcomes.